KAJIAN SOSIOLINGUISTIK BAHASA INDONESIA PADA PETANI DAN BURUH TANI DI KECAMATAN COMAL - Desti; Sri Suciati; Ahmad Ripai; Setia Naka Andrian (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research is based on the use of Indonesian among marginalized communities. In everyday life, Indonesians still does not attract public attention. This research aims to describe the use of Indonesian among farming communities and farm workers in Comal District, Pemalang Regency. This type of research is descriptive qualitative which aims to describe the use of Indonesian in the people of Sikayu Village, Comal District, Pemalang Regency. The data collection technique in this research was carried out using skilled listening and involvement techniques.The results of the research show that in the language variation category, farmers and farm workers predominantly master Javanese. This is confirmed by the results of interviews which state that the most dominant language used is Javanese. Meanwhile, the results of interviews with the speech community category show that farmers and farm workers are already accustomed to using Javanese when communicating or interacting anywhere. Based on the results of this analysis, it can be concluded that the use of Indonesian in the speech community in Sikayu Village, Comal District, Pemalang Regency, is an example of a bilingual community. The use of Indonesian among marginal farmers and farm laborers in Sikayu Village is influenced by social status and the place of use.